2019
DOI: 10.1016/j.ajp.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Community violence exposure and determinants of adolescent mental health: A school-based study of a post-conflict area in Indonesia

Abstract: Introduction: Studies have shown the adverse impact of exposure to community violence on adolescent health. However, most of the studies were conducted in high-income countries. This study aimed at assessing the community violence exposure and the determinants of mental health problems among adolescents in Ambon, a post-conflict area in Indonesia. Material and methods: We conducted a cross-sectional, school-based study involving 511 of 10th-graders from six randomly selected high schools in Kotamadya Ambon. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Although prior research has examined the associations between these factors mentioned above and children’s mental health outcomes empirically, several predictors’ effects remain unclear. For example, the female gender has received mixed support [2, 5, 14]. In addition, the associations between insurance status and children’s mental health status have not been well explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior research has examined the associations between these factors mentioned above and children’s mental health outcomes empirically, several predictors’ effects remain unclear. For example, the female gender has received mixed support [2, 5, 14]. In addition, the associations between insurance status and children’s mental health status have not been well explored.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found that youth living in a post conflict setting have been exposed to some kind of violence in their community (Das-Munshi et al, 2017;Fausiah, Turnip, & Hauff, 2019;Kaminer, du Plessis, Hardy, & Benjamin, 2013;McAloney, McCrystal, Percy, & McCartan, 2009). The fact the community discussed political violence in an ease manner might be a sign of the increasing sense to tolerate violence.…”
Section: Resultsmentioning
confidence: 99%
“…This study focuses on Indonesia's sovereign rights in the North Natuna Sea conflict area due to China's nine-dash line claim (Fausiah et al, 2019;Zou et al, 2021). This study wants to examine (1) the existence of the traditional fishing ground principle in UNCLOS III 1982 (2) The impact of the nine-dash line claim on Indonesia's sovereign rights in the conflict area of the North Natuna Sea.…”
Section: Status Ofmentioning
confidence: 99%